2017
DOI: 10.5851/kosfa.2017.37.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Replacing Pork Meat with Yellow Worm (Tenebrio molitor L.) for Frankfurters

Abstract: The effects of replacing pork meat with yellow mealworms on the physicochemical properties and sensory characteristics of frankfurters were investigated in this study. The control (50% pork ham), T1 (45% pork ham + 5% yellow mealworm), T2 (40% pork ham + 10% yellow mealworm), T3 (35% pork ham + 15% yellow mealworm), T4 (30% pork ham + 20% yellow mealworm), T5 (25% pork ham + 25% yellow mealworm), and T6 (20% pork ham + 30% yellow mealworm) were prepared, replacing lean pork meat with yellow mealworm. The moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
90
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 24 publications
26
90
3
2
Order By: Relevance
“…The pH of the emulsion systems after replacing myofibrillar protein with T. molitor protein was significantly higher ( p < 0.05), and it increased with T. molitor protein concentrations. These results are in agreement with those of Choi et al [ 8 ] who reported that replacing pork meat with yellow mealworm increases the pH of frankfurters. Similarly, Kim et al [ 3 ] reported that the pH of emulsion sausages with mealworm larvae was higher than control without mealworm larvae.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The pH of the emulsion systems after replacing myofibrillar protein with T. molitor protein was significantly higher ( p < 0.05), and it increased with T. molitor protein concentrations. These results are in agreement with those of Choi et al [ 8 ] who reported that replacing pork meat with yellow mealworm increases the pH of frankfurters. Similarly, Kim et al [ 3 ] reported that the pH of emulsion sausages with mealworm larvae was higher than control without mealworm larvae.…”
Section: Resultssupporting
confidence: 93%
“…In addition, the redness and yellowness of the emulsion systems increased significantly ( p < 0.05) with increasing T. molitor protein concentrations. These results are consistent with those by Choi et al [ 8 ] who observed that replacing pork meat with yellow mealworm results in lower lightness and higher yellowness of frankfurters. Smarzyński et al [ 22 ] reported that the color of the product is known to play very important role in the acceptance of customers, and then observed that the respondents dislike the product containing higher concentrations of cricket flour.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations